Practical Bromination Approach to the Synthesis of Dimethyl 6,6’-Bis(bromomethyl)-[2,2’-bipyridine]-4,4’-dicarboxylate - Ou, Wenhua; Liu, Ruonan; Wang, Bo (Letters in Organic Chemistry, 2019)
Dimethyl 6,6’-bis(bromomethyl)-[2,2’-bipyridine]-4,4’-dicarboxylate (2) was synthesized from dimethyl 6,6’-dimethyl-2,2'-bipyridine-4,4'-dicarboxylate (1) through dibromination and debromination. Debromination of dimethyl 6,6’-bis(dibromomethyl)-[2,2’-bipyridine]-4,4’-dicarboxylate (4) with diethyl phosphite and N,N-diisopropylethylamine in THF afforded target product 2 in 58% overall yield. The biggest advantage of the presented method is to avoid so much impurities and the difficulty of purification in the direct bromination method reported previously.
Keywords: debromination